Indomethacin induced gene regulation in the rat hippocampus. Issue 1 (December 2015) - Sathyanesan, Monica; Girgenti, Matthew; Warner-Schmidt, Jennifer; Newton, Samuel
Abstract Background Non-steroidal anti-inflammatory drugs such as indomethacin are widely used to treat inflammatory diseases and manage pain, fever and inflammation in several conditions, including neuropsychiatric disorders. Although they predominantly function by inhibiting cyclooxygenase (COX) activity, important COX-independent actions also occur. These actions could be responsible for the adverse side effects associated with chronic and/or high dose usage of this popular drug class. Results We examined gene regulation in the hippocampus after peripheral administration of indomethacin by employing a microarray approach. Secondary confirmation and the brain expression pattern of regulated genes was examined byin situ hybridization and immunohistochemistry. Transglutaminase 2, serum glucocorticoid inducible kinase, Inhibitor of NF-kappa B and vascular endothelial growth factor were among genes that were prominently upregulated, while G-protein coupled receptor 56 and neuropeptide Y were among genes that were downregulated by indomethacin. Co-localization studies using blood vessel markers revealed that transglutaminase 2 was induced specifically in brain vasculature. Conclusions The data demonstrate that COX-inhibitors can differentially regulate gene transcription in multiple, functionally distinctly cell types in the brain. The results provide additional insight into the molecular actions of COX-inhibitors and indicate that their effects on vasculature could influence cerebral blood flow mechanisms.